2020
DOI: 10.3892/etm.2020.8522
|View full text |Cite
|
Sign up to set email alerts
|

CCNB2, NUSAP1 and TK1 are associated with the prognosis and progression of hepatocellular carcinoma, as revealed by co‑expression analysis

Abstract: The mortality rate associated with hepatocellular carcinoma (HCC) is the third highest among all digestive system tumors. However, the causes of HCC development and the underlying mechanisms have remained to be fully elucidated. In the present bioinformatics study, genetic markers were identified and their association with HCC was determined. The mRNA expression datasets GSE87630, GSE74656 and GSE76427 were downloaded from the Gene Expression Omnibus (GEO) database. A total of 96 differentially expressed genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Except for BUB1B, the mechanisms of the other hub genes in hepatocarcinogenesis have been elucidated to varying degrees ( Foijer et al, 2017 ; Jin et al, 2020 ; Li et al, 2014 ; Li, Bai & Zhang, 2017 ; Liu et al, 2020 ; Wu et al, 2018b ; Yang, Lin & Liu, 2020 ). Therefore, the relationship between BUB1B and other hub genes was investigated first.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for BUB1B, the mechanisms of the other hub genes in hepatocarcinogenesis have been elucidated to varying degrees ( Foijer et al, 2017 ; Jin et al, 2020 ; Li et al, 2014 ; Li, Bai & Zhang, 2017 ; Liu et al, 2020 ; Wu et al, 2018b ; Yang, Lin & Liu, 2020 ). Therefore, the relationship between BUB1B and other hub genes was investigated first.…”
Section: Resultsmentioning
confidence: 99%
“…CCNB1, CCNB2, CDK1 and CDC20, are all cell cycle-related proteins. Many studies have demonstrated their oncogenic roles in the regulation of cell cycle progression in a series of tumors, such as hepatocellular carcinoma ( Jin et al, 2020 ; Li et al, 2014 ; Liu et al, 2020 ; Wu et al, 2018a ), bladder cancer ( Heo et al, 2020 ; Kim et al, 2014 ), non-small lung cancer ( Qian et al, 2015 ; Wang et al, 2019a ), pancreatic cancer ( Wei et al, 2013 ; Zhang et al, 2018 ) and breast cancer ( Kidokoro et al, 2008 ; Kim et al, 2012 ; Parmar et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of CCNB2 malregulates spindle checkpoints in the cell cycle and leads to chromosomal instability, one of the signature phenotypes of most cancers. [20][21][22] CCNB2 regulates the activity of cyclin-dependent kinases. It is well known that different cyclins can regulate the eukaryotic cell cycle through CDK at specific points in the mitotic cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of CCNB2 malregulates spindle checkpoints in the cell cycle and leads to chromosomal instability, one of the signature phenotypes of most cancers. [20–22]…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of nucleolar and spindle-associated protein 1 (NUSAP1) has been identified as a robust clinical biomarker of aggressive prostate cancer and is part of two commercial prognostic gene expression panels used to analyze prostate tissue samples [ 2 , 3 , 4 , 5 ]. Over the past decade, increased expression of NUSAP1 has been shown to be associated with poor outcomes in many solid tumors, including those of the skin [ 6 , 7 ], breast [ 8 , 9 , 10 , 11 ], prostate [ 2 , 3 , 12 ], cervix [ 13 , 14 ], brain [ 15 , 16 , 17 ], liver [ 18 , 19 , 20 ], pancreas [ 21 , 22 ], stomach [ 23 , 24 ], ovary [ 25 , 26 ] and lung [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%